PELAYANAN PARKIR DI RUMAH SAKIT ARIFIN NU’MANG KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Gustiar Latif; Erfina Erfina; Kamaruddin Sellang (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
This writing aims to determine the parking services at Arifin Nu'mang Hospital, Panca Rijang District, Sidenreng Rappang Regency, and to determine the factors that affect parking services at Arifin Nu'mang Hospital, Panca Rijang District, Sidenreng Rappang Regency.The population of this writing is 876 visitors, while the sample is 90 visitors. Data collection techniques used in this writing are using observation techniques, interviews, literature study and questionnaires. The collected data were then analyzed using frequency and percentage tables.The results of this paper indicate that the parking service at Arifin Nu'mang Hospital, Panca Rijang District, Sidenreng Rappang Regency with a percentage of 68.6% is in good category, while the factors that affect parking services at Arifin Nu'mang Hospital, Panca Rijang District, Sidenreng Regency Rappang with a percentage of 69.5% with a good category.